THE RELATIONSHIP BETWEEN THE COTININE LEVEL IN URINE AND VITAMIN D IN THE UNIVERSITY STUDENTS - Ayse Berivan Bakan; Naim Uzun; Senay Karadag Arli; Metin Yıldız (Belitung Nursing Journal, 2020)
Background: Vitamin D deficiency is today acknowledged as a pandemic. Vitamin D deficiency and insufficiency are associated with many chronic diseases, including common cancers, cardiovascular diseases, metabolic syndrome, and infectious and autoimmune diseases. Objective: This study aims to investigate the relationship between the cotinine level in urine and Vitamin D. Methods: This study employed a descriptive and relational screening design. It was conducted with 74 smoking university students between January 2019 and March 2020. Data were collected through socio-demographic form and Fagerstrom test for nicotine dependence. Besides, the participating students’ blood and urine samples were taken in a suitable environment. Results: The average age of the participating students was 21.50±2.09. Of all the students, 71.6% were males, 62.2% were exposed to the sun between 12 p.m. and 2 p.m., and the average number of cigarettes smoked daily was 13.52±8.22. The average Vitamin D level in blood was 32.4±15.3 (ng/mL), and the average cotinine level in urine was 1.60 ± .32 (ng/L). No statistically significant relationships were found between the Vitamin D level and the cotinine level (p<0.05). Conclusion: Smoking causes diseases and death in many people, and it is a changeable risk factor. Nursing practices on the struggle against smoking are effective. No significant relationships were found between the Vitamin D level in blood and cotinine level in urine. Similar studies are recommended to be conducted with larger groups and participants from different age groups.